1993
DOI: 10.1007/bf01628318
|View full text |Cite
|
Sign up to set email alerts
|

One further case of unusual origin of three hepatic arteries

Abstract: This article describes a triple vascularization of the liver which is not a common vascular anomaly. Dealing with this particular kind of vascularization, we note the following: a main hepatic a. which enters in the right lobe of the liver and two accessory arteries, the right hepatic a. (a branch of the superior mesenteric a.) and left hepatic a. (from the left gastric a.). In the same way, the cystic a. has an unusual origin: the right accessory hepatic artery. The whole hepatic pedicle was dissected, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…In present study, in all cases proper hepatic artery divided into its terminal branches extrahepatically, of which 92% the point of division was proximal to the point of union of hepatic duct, whereas in 8% cases the point of division was higher, these findings were well in accordance with the reports of Almenar-Garcia (1993) 10 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In present study, in all cases proper hepatic artery divided into its terminal branches extrahepatically, of which 92% the point of division was proximal to the point of union of hepatic duct, whereas in 8% cases the point of division was higher, these findings were well in accordance with the reports of Almenar-Garcia (1993) 10 .…”
Section: Discussionsupporting
confidence: 93%
“…In present study, total 6.5% variation of branching pattern of the common hepatic artery was observed of which 5% were cases of aberrant or accessory hepatic artery and 1.5% cases of trifurcation of common hepatic artery with absence of proper hepatic artery .Whereas as much as 40% of the total variations of branching pattern of the common hepatic artery have been described by Michels (1953) 15 Presence of both accessory right and left hepatic arteries in conjunction with a proper hepatic artery has been described with a 1% incidence by Almenar-Garcia et al(1993) 10 . In his study, Gruttadauria et al (2001) 4 observed the most common anomaly was a replaced/accessory RHA arising from the SMA in 15% of cases; aberrant hepatic artery may be accessory or replacing artery.…”
Section: Discussionmentioning
confidence: 97%